(untitled) (Sains Humanika, 2018)
The development of communication and information technology (ICT) has been developed by the government since the 1980s. This development has contributed to the increasing use of the internet as a new medium for the purpose of partnership, business and knowledge. This socio-cultural change, based on the new media, has led to the receipt of information and forming a new environment in all aspects including religious life. The development of the internet in Malaysia has given a direct impression on the development of Islamic da’wah. Today’s society gains exposure to Islam easily through social media such as facebook, newsgroups, e-groups and others. Therefore, this article aims to examine the impact of the new media toward Islamic da’wah. Data was obtained on library research through secondary data such as journal articles, government reports, books etc. Analysis shows that the flooding of Islamic information in the new media has affected the daâ€™wah among internet users especially in the acceptance of Islamic understanding in aqidah, ibadah and akhlak